A Comunidade epifítica vascular em fragmentos de Floresta Ombrófila Mista no Parque Estadual de Vila Velha, Ponta Grossa – Paraná” - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
We know that the Atlantic Forest is the Brazilian biome with the greatest wealth of plant species, considered a global biodiversity hotspot, this biome also housing the greatest diversity of vascular epiphytes in Brazil. Epiphytes are plants that use other plant species as substrate, without causing any damage to the phorophyte and providing various ecosystem services to the forest, being a fundamental part of the ecological dynamics of this environment. Realizing the scarcity of data on the vascular epiphytes of Campos Gerais, this work brings the study of vascular epiphytes in Fragments of Mixed Ombrophylous Forest (FOM) of the Vila Velha State Park (PEVV), Ponta Grossa, Paraná. Chapter 1 refers to the floristic composition in 3 areas: Lagoa Dourada, Trilha do Bosque and Mata da Fortaleza. 85 species of vascular epiphytes were recorded, distributed in 39 genera and 11 families. The families with the greatest species richness were: Orchidaceae with 27 species (31.7%), followed by Bromeliaceae with 15 species (20.3%) and Polypodiaceae with 12 species (14.1%), the majority were holoepiphytes. The second chapter deals with the phytosociological dynamics in Mata da Fortaleza, the largest remnant of Atlantic Forest within the PEVV. After processing the data, it was possible to state that the species studied with the highest Epiphytic Importance Value (VIE) are from the Polypodiaceae and Bromeliaceae family, with Cactaceae and Orchidaceae also being denoted next. The results obtained in this research elucidated still unknown aspects of vascular epiphytes, as well, will serve as a basis for conservation and adequate maintenance of the environment in which these plants are located.
Keywords: Comunidade epifítica; Unidade de Conservação; Dinâmica fitossociológica; Epiphytic community; Conservation Unit; Phytosociological dynamics; CNPQ::CIENCIAS BIOLOGICAS